Sistem Pemerintahan, Politik dan Peran Ahlu Hall Wal ‘Aqdi pada Masa Khulafaur Rasyidin - Abdul Latif Rahmat; Kholid Mawardi (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2024)
This study aims to analyze the government system and the role of Ahl Al-Hall wa Al-'Aqd during the khulafaurrosyidin era, which started with the government system of Abu Bakar, Umar Bin Khottab, Ustman Bin 'Affan and Ali bin Abi Talib. The method used in this literature is carried out by examining the concepts and theories used based on the available literature, which includes books, articles published in scientific journals which contain theories relevant to research problems. The results of this study are that overall the appointment of khalifaurrasyidin is carried out by way of deliberation. Even though at the moment of selecting the caliph one with the other caliphs had different problems to reach an agreement on the election of the caliph. This is natural, so that the different problems he experienced gave birth to different efforts between one caliph and another. Ahl Al-Hall wa Al-Aqd are people who have contributed to realizing the replacement of the caliph after the death of the Prophet Muhammad SAW. Keywords: Government System and Role of Ahl Al-Hall wa Al-Aqd